2019
DOI: 10.1016/j.devcel.2019.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Basal Protrusions Mediate Spatiotemporal Patterns of Spinal Neuron Differentiation

Abstract: Summary During early spinal cord development, neurons of particular subtypes differentiate with a sparse periodic pattern while later neurons differentiate in the intervening space to eventually produce continuous columns of similar neurons. The mechanisms that regulate this spatiotemporal pattern are unknown. In vivo imaging in zebrafish reveals that differentiating spinal neurons transiently extend two long protrusions along the basal surface of the spinal cord before axon i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…We provided evidence that basal protrusions developed by differentiating neurons may spatially and temporally regulate the pattern of neuronal differentiation through long-range Delta-Notch-mediated lateral inhibition. This was further confirmed by mathematical modelling that showed the positioning and timing of neuronal differentiation cannot be explained by Delta-Notch signalling occurring between immediate neighbours but can be explained by the basal protrusions delivery of long-range Delta-Notch-mediated lateral inhibition [54].…”
Section: Cellular Protrusions Developed By Differentiating Neurons Inmentioning
confidence: 67%
See 4 more Smart Citations
“…We provided evidence that basal protrusions developed by differentiating neurons may spatially and temporally regulate the pattern of neuronal differentiation through long-range Delta-Notch-mediated lateral inhibition. This was further confirmed by mathematical modelling that showed the positioning and timing of neuronal differentiation cannot be explained by Delta-Notch signalling occurring between immediate neighbours but can be explained by the basal protrusions delivery of long-range Delta-Notch-mediated lateral inhibition [54].…”
Section: Cellular Protrusions Developed By Differentiating Neurons Inmentioning
confidence: 67%
“…Although it conventionally occurs between immediate neighbours, in Drosophila, Notch-Delta signalling has been shown to operate over larger distances to pattern mechanosensory bristles [51][52][53][54][55][56]. We recently showed that this can occur in the vertebrate neural tube [54]. All recently born neurons in the zebrafish spinal cord extend two long protrusions along the basal surface of the spinal cord that span several neural progenitors ( Figure 2).…”
Section: Cellular Protrusions Developed By Differentiating Neurons Inmentioning
confidence: 99%
See 3 more Smart Citations